Review Concerning Violence. Directed by Göran Olsson. Produced by Final Cut for Real, Helsinki Filmi Oy, Louverture Films. 2014 - Murrey, A (SAGE Publications, 2015)
Göran Olsson’s filmic account of what is perhaps Frantz Fanon’s (1961) most famous chapter in The Wretched of the Earth, “Concerning Violence,” opens as a soldier, from his secure vantage point in a hovering helicopter, shoots a horned bull as it races across an open field. The animal is shot with the automatic gunfire and stumbles, its knees buckling and head stooping. Convulsing painfully in the dirt, the shooting continues until a bullet pierces the inner nostril. Blood pours from the animal’s nose in a thick, constant stream as his movements slow. Lauryn Hill’s powerful voice is heard, quoting Fanon, “Colonialism is not a thinking machine, nor a body endowed with reasoning faculties. It is violence in its natural state, and it will only yield when confronted with greater violence.” The dying bull, crudely shot from above without any intention of providing nutrition to the passing soldiers, embodies the illogical and brutal suffering effected upon colonized people through colonial violence. Olsson’s film is a powerful aesthetic backdrop for Fanon’s anti-colonial manifesto, one that unflinchingly engages with colonialism as a violent project. Against this illogical violence, counter-violence becomes a crucial component of emancipation. The film opens up new spaces for considerations of the use of violence in the face of terrible, absolute, and normalized violence, including today’s anti-racist, anti-sexist, and anti-capitalist movements, poised as they are against enormous infrastructures of normalized and everyday violence.